2016
DOI: 10.22630/eiogz.2016.113.3
|View full text |Cite
|
Sign up to set email alerts
|

Żywność ekologiczna w opinii młodych polskich konsumentów – wyniki badań

Abstract: The aim of this paper is to show how organic food is perceived by young Polish consumers – what are their opinions on this kind of food and its producers, what qualities they attribute to it and whether they recognize the differences between organic and conventional food. To achieve the purpose, the literature on consumer behavior, organic farming and food produced under its conditions was analysed. Moreover, primary research was conducted by the authors in February and March 2014 by means of an audito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Mróz [106] discussed that the behavior of Polish consumers runs counter to the archetype of sustainable consumption. Escher and Petrykowska [107] suggested a positive attitude of young people to the idea of ecological consumption and green purchasing. Young consumers see the positive features of green products and see the positive impact of their production on the condition of the ecosystem, but this study confirmed that these positive attitudes do not always translate into actual purchasing decisions [107].…”
Section: Discussionmentioning
confidence: 99%
“…Mróz [106] discussed that the behavior of Polish consumers runs counter to the archetype of sustainable consumption. Escher and Petrykowska [107] suggested a positive attitude of young people to the idea of ecological consumption and green purchasing. Young consumers see the positive features of green products and see the positive impact of their production on the condition of the ecosystem, but this study confirmed that these positive attitudes do not always translate into actual purchasing decisions [107].…”
Section: Discussionmentioning
confidence: 99%
“…Younger consumers are more sensitive and concerned about issues related to sustainable development 23,24 than older consumers, and they are increasingly interested in more sustainable behavior, such as buying green products 25 . In addition, the younger generation has acquired relevant environment-related knowledge through environmental education and is inclined to adopt practices that respect the natural environment 26 . As expected, respondents whose monthly income rarely and never covered their household expenditure expressed a willingness to purchase fewer circular products when compared to those whose income always covered expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…Younger generations of consumers also perceive organic food products as environmentally responsible, and are less likely to suspect their producers and distributors of manipulation or unethical practices. [Escher and Petrykowska 2016].…”
Section: Introductionmentioning
confidence: 99%